Teaching Nonauthoritarian Clinical Ethics: Using an Inventory of Bioethical Positions - Fiester, Autumn (The Hastings Center report, 2015)
One area of bioethics education with direct impact on the lives of patients, families, and providers is the training of clinical ethics consultants who practice in hospital-based settings. There is a universal call for increased skills and knowledge among practicing consultants, broad recognition that many are woefully undertrained, and a clear consensus that CECs must avoid an “authoritarian approach” to consultation—an approach, that is, in which the consultant imposes his or her values, ethical priorities, or religious convictions on the stakeholders in an ethics conflict. Yet little work has been done on how to teach CECs not to impose their values in an ethics consultation, or even on the dimensions of this problem. In this essay, I propose a tool for bioethical instruction that targets this question: how can CECs be taught a nonauthoritarian mode of ethical analysis and consultation that can avert the problem of values imposition?